KUALITAS BUTIR SOAL SUMATIF TENGAH SEMESTER (STS) BUATAN GURU PADA MATA PELAJARAN BAHASA INDONESIA KELAS III SDN 11 PANGKALPINANG - Suryadin, Asyraf; Della Fitria (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze the Summative Middle Semester multiple choice question grain of Indonesian Language grade III elementary school Public 11 Pangkalpinang based on the index of difficulty, differential power, confounding effectiveness, validity and reliability. The method of data collection in this study was the descriptive quantitative approach documentation method. Based on the results of the study found the difficulty level was not good but had sufficient differential power, question tampering was effective or already good, question validity was categorized as high and reliability scores were still low with unreliable status. However some questions are revised or need to be replaced with other question grain especially the questions which are still poor. The results of this study are expected to reference teachers in improving the preparation of subsequent Mid-Semester Summative (STS) questions.